ANALISIS KONDISI SANITASI LINGKUNGAN TERKAIT PENCEMARAN TOTAL COLIFORM TERHADAP AIR TANAH DI KELURAHAN TEBET BARAT - Endah Yunari N; Soleha Ismi Azhom (FT-USNI, 2018)
The majority of RW 07 residents use groundwater daily. While flood and still water often happens and the inadequately of wastewater management are one of many problems RW 07 residents faced. The purpose of this research are to be able to identify sanitation condition in residential area and identify the bacteriological quality of groundwater in West Tebet Urban Village, and analyze the relationship between those variable. Total coliform test of groundwater procured from the local well using Most Probable Number (MPN) method. This research showed that the amount of total Coliform ranging from 3/ 100 ml to >240.000/ 100 ml and as much as 83% of groundwater in local wells have surpassed the amount Total Coliform standard which Indonesian Health Ministry regulated in No. 416/ Menkes/ IX/ 1990. Other than that, the result showed that there is no relation between septic tank and drainage distance also well depth to the amount of Total Coliform.